THE REGULATION OF PUBLIC ACCOUNTING IN FRANCE. - Wasserman, Max J. (The Accounting Review, 1931)
The article proposes to discuss the regulation, by governmental authority, of the profession of public accountancy in France with particular reference to the newly created diploma, of Expert-Comptable Reconra par l'Etat. The role of the French public accountant and consequently the importance of the new decree affecting the profession and giving its members an official title and status may be more dearly grasped if the main characteristics of private accounting practice in France are first briefly sketched. To the U.S., the French public accountant is obliged to ply his trade in some what antiquated surroundings. The business technique of the French resembles the U.S. practice which prevailed at the beginning of this century rather than that of the present time. Compared to the U.S. business organization, that of the French is less formal and more personal, more human than mechanical, traditional rather than efficient, conservative rather than aggressive. While then are many large units, France is generally considered the country of small, personal and family enterprises.